Construction of the Ohio Children's Opportunity Index - Fareed, Naleef; Singh, Priti; Jonnalagadda, Pallavi; Swoboda, Christine; Odden, Colin; Doogan, Nathan (Frontiers in Public Health, 2022)
Objective: To describe the development of an area-level measure of children’s opportunity, the Ohio Children’s Opportunity Index (OCOI). Data Sources/Study Setting: Secondary data were collected from US census based-American Community Survey (ACS), US Environmental Protection Agency, US Housing and Urban Development, Ohio Vital Statistics, US Department of Agriculture-Economic Research Service, Ohio State University Center for Urban and Regional Analysis, Ohio Incident Based Reporting System, IPUMS National Historical Geographic Information System, and Ohio Department of Medicaid. Data were aggregated to census tracts across two time periods. Study Design: OCOI domains were selected based on existing literature, which included family stability, infant health, children’s health, access, education, housing, environment and criminal justice domains. The composite index was developed using an equal weighting approach. Validation analyses were conducted between OCOI and health and race-related outcomes, and a national index. Principal Findings: Composite OCOI scores ranged from 0-100 with an average value of 74.82 (SD, 17.00). Census tracts in the major metropolitan cities across Ohio represented 76% of the total census tracts in the least advantaged OCOI septile. OCOI served as a significant predictor of health and race-related outcomes. Specifically, the average life expectancy at birth of children born in the most advantaged septile was approximately nine years more than those born in least advantaged septile. Increases in OCOI were associated with decreases in proportion of Black (48 points lower in the most advantaged vs least advantaged septile), p<0.001) and Minority populations (54 points lower in most advantaged vs least advantaged septile, p<0.001). We found R-squared values >0.50 between the OCOI and the national Child Opportunity Index scores. Temporally, OCOI decreased by 1% between the two study periods, explained mainly by decreases in the children health, accessibility and environmental domains. Conclusion: As the first opportunity index developed for children in Ohio, the OCOI is a valuable resource for policy reform, especially related to health disparities and health equity. Health care providers will be able to use it to obtain holistic views on their patients and implement interventions that can tackle barriers to childhood development using a more tailored approach.